Les apprentissages d’un RETEX scientifique et collectif sur l’ouragan Irma (saison cyclonique 2017, Petites-Antilles du Nord, projet ANR TIREX) - Frédéric Leone; Yann Bérard; Stéphanie Defossez; Jérémy Desarthe; Virginie Duvat; Delphine Grancher; Philippe Palany; Narcisse Zahibo (EchoGéo)
This article looks back at the 2017 hurricane season, which strongly impacted the Lesser Antilles, particularly during the passage of Hurricane Irma over the islands of Saint-Martin and Saint-Barthélemy. It presents the main results of a collective and multi-dimensional scientific feedback, conducted over five years as part of the ANR TIREX research project. In addition to the many lessons learned, the project explores ways of transferring scientific knowledge to the population and decision-makers, and questions the practice of RETEX in general. In particular, TIREX contributes to improve hurricane warnings, to identify inherited vulnerability factors, to understand the damage processes related to wind and sea, to monitor the dynamics of territorial and human recovery at the individual and collective levels, and more generally to strengthen the adaptation and response capacities of Lesser Antilles societies in the face of hurricanes.